2021
DOI: 10.1007/s00590-021-02880-x
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus effect on rates of perioperative complications after operative treatment of distal radius fractures

Abstract: Purpose This study focuses on distal radius fractures that require surgical treatment. Patients with diabetes mellitus (DM) are at increased risk of bone fracture despite normal areal bone mineral density. The aim of this study is to identify the impact of DM on perioperative complications for patients undergoing operative treatment of distal radius fracture. Methods A retrospective cohort study was conducted using data collected through the National Surgical Quality Improvement Program database. All patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…This subgroup analysis is biased by very large, retrospective registry studies, which are unreliable for detecting SSI because they rely solely on valid recording and coding (Leaper et al, 2013;Smyth and Emmerson, 2000). Looking at the largest included studies, the SSI risk ranges from 0.1% to 2.3% in studies with over 10,000 participants (Constantine et al, 2022;Galivanche et al, 2021;Mahmood Wei et al, 2021). These four studies are all on distal radial fracture fixation, mostly ORIF, and all are retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…This subgroup analysis is biased by very large, retrospective registry studies, which are unreliable for detecting SSI because they rely solely on valid recording and coding (Leaper et al, 2013;Smyth and Emmerson, 2000). Looking at the largest included studies, the SSI risk ranges from 0.1% to 2.3% in studies with over 10,000 participants (Constantine et al, 2022;Galivanche et al, 2021;Mahmood Wei et al, 2021). These four studies are all on distal radial fracture fixation, mostly ORIF, and all are retrospective.…”
Section: Discussionmentioning
confidence: 99%
“…Wei et al conducted a retrospective review of 11,272 patients and found that increased operation time was associated with increased risk of reoperation following DRF repair ( P < 0.001). 32 They suggested that resident training and inexperience was the main catalyst for this effect. Our study suggests that BMI is associated with this phenomenon, as increased BMI was associated with both longer operation times and increased reoperation rates in our analysis.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Previous studies evaluating diabetes as a risk factor following DRF surgery demonstrated polarity in outcomes with one report indicating increased complications and another reporting minimal effect on complications. 32,33 report's finding that diabetes approaches but does not meet significance (P = .09) may be reflective of this discrepancy. In addition, BMI approached but did not meet significance (P = .086) on multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%